2019
DOI: 10.48550/arxiv.1910.03544
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Find or Classify? Dual Strategy for Slot-Value Predictions on Multi-Domain Dialog State Tracking

Abstract: Dialog State Tracking (DST) is a core component in task-oriented dialog systems. Existing approaches for DST usually fall into two categories, i.e, the picklistbased and span-based. From one hand, the picklist-based methods perform classifications for each slot over a candidate-value list, under the condition that a predefined ontology is accessible. However, it is impractical in industry since it is hard to get full access to the ontology. On the other hand, the span-based methods track values for each slot t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(62 citation statements)
references
References 23 publications
(66 reference statements)
0
60
0
Order By: Relevance
“…Intent Classification Intent classification aims to identify the intents of user utterances, which is a critical component of goal-oriented dialog systems. Attaining high intent classification accuracy is an important step towards solving many downstream tasks such as dialogue state tracking Zhang et al, 2019) and dialogue management (Gao et al, 2018;Ham et al, 2020). A practical challenge is data scarcity because different systems define different sets of intents, and it is costly to obtain enough utterance samples for each intent.…”
Section: Semantic Textual Similaritymentioning
confidence: 99%
“…Intent Classification Intent classification aims to identify the intents of user utterances, which is a critical component of goal-oriented dialog systems. Attaining high intent classification accuracy is an important step towards solving many downstream tasks such as dialogue state tracking Zhang et al, 2019) and dialogue management (Gao et al, 2018;Ham et al, 2020). A practical challenge is data scarcity because different systems define different sets of intents, and it is costly to obtain enough utterance samples for each intent.…”
Section: Semantic Textual Similaritymentioning
confidence: 99%
“…, 2007;Williams et al, 2014). Recent state-of-the-art models (Lei et al, 2018;Wu et al, 2020;Peng et al, 2020;Zhang et al, 2019;Heck et al, 2020;Mehri et al, 2020;Hosseini-Asl et al, 2020; trained with extensive annotated dialogue data have shown promising performance in complex multi-domain conversations (Budzianowski et al, 2018;. However, collecting large amounts of data for every dialogue domain is often costly and inefficient.…”
Section: Related Workmentioning
confidence: 99%
“…Slot Value. Following recent works (Zhang et al, 2019;, slots are divided into categorical and non-categorical slots. For categorical slots, we incorporate the candidate values into the slot description, i.e., "[slot] of the [domain] is [value-1] or [value-2]?".…”
Section: Slot Description Variantsmentioning
confidence: 99%